2019
DOI: 10.7150/jca.29072
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial of probiotics to reduce severity of physiological and microbial disorders induced by partial gastrectomy for patients with gastric cancer

Abstract: Gastrectomy has been widely used for the treatment of gastric cancer, and the severity of physiological and microbial disorders has greatly harmed the health of patients. In the present study, a probiotic combination containing Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis and Bacillus cereus was used to reduce the physiological disorders induced by gastrectomy via monitoring the blood index and microbial diversity using high-throughput sequencing. Our results indicated that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…Theαvalue was set to 0.05 in order to correct multiple comparisons. Finally, we used Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) to analyze the metabolic function and its influence on the host cell of bacteria in Kyoto Encyclopedia of Genes and Genomes (KEGG) functional spectrum database ( Liu et al., 2019 ; Zheng et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Theαvalue was set to 0.05 in order to correct multiple comparisons. Finally, we used Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUST) to analyze the metabolic function and its influence on the host cell of bacteria in Kyoto Encyclopedia of Genes and Genomes (KEGG) functional spectrum database ( Liu et al., 2019 ; Zheng et al., 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous studies, orally taking of probiotics drugs during radiotherapy, chemotherapy and surgery in patients can significantly reduce their side effects by improving the disorder of intestinal microbiota 94 , 95 . Other works also indicated that dietary supplements (prebiotics) 96 or prebiotics 97 could selectively stimulate the growth and activity of internal probiotics to reduce the disorder of intestinal microbiota.…”
Section: Future Directionsmentioning
confidence: 99%
“…Patients with colon cancer that received probiotics, Bifidobacterium lactis Bl-04 and Lactobacillus acidophilus NCFM had an increased abundance of butyrate-producing bacteria, especially Faecalibacterium and Clostridiales spp in the tumour, non-tumour mucosa and faecal microbiota, resulting in the reduction of colorectal cancer-associated genera such as Fusobacterium and Peptostreptococcus 71. Recent study showed that a probiotic combination containing Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis and Bacillus cereus reduced the physiological disorders induced by gastrectomy 72. Another randomized, double-blind, placebo-controlled trial showed that probiotics reduced the severity of oral mucositis induced by chemoradiotherapy for patients with nasopharyngeal carcinoma 73.…”
Section: Clinical Trials Of Probioticsmentioning
confidence: 99%